Acceptability and compliance with a remote monitoring system to track smoking and abstinence among young smokers - McClure, Erin A. (Am J Drug Alcohol Abuse, 2018)
BACKGROUND: Similar to adult smokers, quit attempts among younger smokers almost inevitably result in relapse. Unlike adults, less is known about the process of relapse in this younger age group. A technology-based remote monitoring system may allow for detailed and accurate characterization of smoking and abstinence and would help to improve cessation strategies. OBJECTIVES: This study describes a mobile system that captures smoking using breath carbon monoxide (CO) and real-time self-reports of smoking behavior. Compliance, feasibility, acceptability, and accuracy of the system were measured during a quit attempt and subsequent monitoring period. METHODS: The mobile application (My Mobile Monitor; M(3)) combined breath CO with ecological momentary assessment, delivered via smartphone. Participants (N=16; 75% female) were daily smokers between the ages of 19-25, who used the app for 11 days during which they agreed to make a quit attempt. Acceptability, compliance, and abstinence were measured. RESULTS: Participants averaged 22.3 ± 2.0 years old and smoked an average of 13.0 ± 6.1 cigarettes per day. Overall session compliance was 69% and during the quit attempt, 56% of participants abstained from smoking for at least 24 hours. Agreement between self-reported smoking compared to breath CO was generally high, when available for comparison, though underreporting of cigarettes was likely. CONCLUSIONS: This study demonstrates feasibility of a remote monitoring app with younger smokers, though improvements to promote compliance are needed. Remote monitoring to detect smoking and abstinence represents a step forward in the improvement of cessation strategies, but user experience and personalization are vital.